Analysis of Lexical, Grammatical and Stylistic Transformations in "The Prince and The Pauper". - Inogomjonova Robiya Rustamjon Qizi (Zien Journals, 2024)
This article analyzes transformations in Mark Twain's "The prince and the pauper". At the beginning of the article, the writer's life and work, as well as several famous works are discussed. The lexical, grammatical, and stylistic aspects of the language are skillfully explained in the example of this work.
Keywords: simile; allusion; metaphor